Efficacy of a Mobile Texting App (HepTalk) in Encouraging Patient Participation in Viral Hepatitis B Care: Development and Cohort Study - Hyun, Chul; McMenamin, Joseph; Ko, Okhyun; Kim, Soonsik (JMIR Publications, 2020)
BackgroundChronic hepatitis B virus (HBV) infection is a major cause of liver-related morbidity and mortality among Asian Americans in the United States. Despite the available resources, a majority of HBV-infected individuals are not able to access adequate health care owing to numerous barriers. ObjectiveThis study aimed to assess the efficacy of a newly developed mobile texting app (HepTalk) in overcoming these barriers and improving patient engagement and health care access among HBV-infected and nonimmune individuals. MethodsHepTalk was employed for two-way communication between participants and patient navigators. A total of 82 Korean American participants who were either HBV infected or nonimmune to HBV, identified from a community hepatitis B campaign in New York, were enrolled in the study. After informed consent was obtained, both the frequency and themes of the text messages were evaluated. The effects of this communication on linkage to care at the end of the 6-month intervention period were analyzed and discussed. ResultsOn average, patient navigators sent and received 14 and 8 messages per participant, respectively, during the 6-month period. The themes of the messages were similar to the following 4 categories: finding providers, scheduling appointments with providers, health education, and financial issues. Of the 82 participants, 78 were linked to care within 6 months (a 95% linkage rate). ConclusionsHepTalk may be employed as an effective and strategic tool to facilitate communicative interaction between patients and patient navigators or health care providers, thereby improving patient engagement and health care access.